The Influence of Birth Ball on Fear in the Delivery Process - Delis Fatimatuzzahro; Feva Tridiyawati (Global Health Science Group, 2023)
The fear of childbirth caused by pain can cause stress which causes excessive release of stress hormones resulting in smooth muscle tension and vasocontric blood vessels resulting in decreased uterine contractions, decreased uteroplacental circulation, reduced blood flow and oxygen to the uterus. One of the management of fear reduction is using birth balls. The purpose of this study was to analyze the effect of birth ball intervention on reducing fear in maternity mothers. This research is a type of intervention research with experimental quasy design. The location used for this research is at PMB Bd. Aisyah Mandalawangi-Pandeglang - Banten in May – June 2023. The sample used in this study was 33 respondents and was selected using purposive sampling. Statistical analysis using independent t test. The average fear score before the intervention was 62.76 and the average fear score after the birth ball intervention was 57.42. The results of the independent t test obtained Sig.2-tailed values of 0.015 < 0.05.